Key Factors Influencing the Consumer Adoption of Mobile Wallets in Nepal - Karki, Sagar; Shrestha, Nikesh; Pokharel, Suresh (International Journal on Engineering Technology, 2024)
Over recent years, mobile wallets have seen rapid development and increased demand, especially during and after the COVID-19 pandemic. Their usage has surged, with various studies examining user intentions and perspectives toward mobile wallets in countries like Malaysia, India, Ghana, and Tanzania. However, such research in Nepal is lacking, highlighting the need for this study. The research integrates the Technological Acceptance Model (TAM) and behavioral elements to create a conceptual model aimed at identifying key determinants influencing users' willingness to use mobile wallets. Using TAM and Innovation Resistance Theory, the study employs a descriptive research approach and quantitative model, gathering numerical data via a self-administered questionnaire. A non-probability sampling technique was used to collect 417 samples among the wallet users in Kathmandu. The findings indicate that UF is the most influential factor among all, based on rank analysis with a mean value (M = 3.954) and a Beta value of 0.271. The results demonstrate a significant relationship between UF, IF, and VF, with |t(417)| = 0.000, 0.000, 0.001 and p-values < 0.05. Conversely, RF, TF, and PCF showed no significant relationships, with |t(417)| = 0.933, 0.178, and 0.065, and p-values > 0.05. Additionally, TF exhibited a positive link with consumer adoption of mobile wallets among those aged 35 and above; |t(32)| = 0.012, p < 0.05. The correlation coefficient (R = 0.595) further indicates a positive correlation.The ANOVA results show a p-value of 0.000, which is below the alpha level of 0.01, confirming the model as a good predictor of the relationship between dependent and independent variables. The F-ratio value of 37.642 is significant at the 1% level, indicating that the regression model has achieved a satisfactory level of goodness-of-fit in predicting the variance in consumer adoption of mobile wallets in relation to the six independent variables, as measured by R, R-squared, and F-ratio values.These results provide a comprehensive understanding of factors influencing mobile wallet adoption in Nepal, valuable to business professionals conducting online transactions via mobile devices. The study's insights into consumer adoption intentions offer a foundation for future research to delve deeper into the factors affecting mobile wallet uptake.